The Ghana heart initiative – a health system strengthening approach as index intervention model to solving Ghana’s cardiovascular disease burden - Doku, Alfred K.; Tetteh, John; Edzeame, Juliette; Peters, Ron J. G.; Agyemang, Charles; Otchi, Elom Hillary; Yawson, Alfred Edwin (Frontiers in Public Health, 2024)
Cardiovascular diseases (CVD) are the leading cause of death worldwide, with 80% of these deaths occurring in low-middle income countries (LMICs). In Ghana and across Africa, CVDs have emerged as the leading causes of death primarily due to undetected and under treated hypertension, yet less than 5% of resources allocated to health in these resource-poor countries go into non-communicable diseases (NCD) including CVD prevention and management. Consequently, most countries in Africa do not have contextually appropriate and sustainable health system framework to prevent, detect and manage CVD to achieve Universal Health Coverage (UHC) in CVD care through improved Primary Health Care (PHC) with the aim of achieving Sustainable Development Goals (SDG) in CVD/NCD. In view of this, the Ghana Heart Initiative (GHI) was envisaged as a national strategy to address the identified gaps using a health system and a population-based approach to reduce the national burden of CVDs. The GHI intervention includes the development of guidelines and training manuals; training, equipment support, establishment of a national call/support center, and improvement in the national data capturing system for CVDs and NCD, management of Hypertension, Deep Vein Thrombosis (DVT) and Heart Failure (HF). Following the implementation of the GHI concept, a national CVD Management Guideline was developed and 300-health facilities across the different levels of care including one teaching hospital, was also supported with basic life-saving equipment. In addition, more than 1,500 healthcare workers also reported improvement in their knowledge and skills in the management and treatment of CVD-related cases in their health facilities. These are key contributions to strengthening the health system for CVD care and learning lessons for scale up.